2005
DOI: 10.1371/journal.pmed.0020164
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Therapy in Postherpetic Neuralgia: A Quantitative Systematic Review

Abstract: BackgroundPostherpetic neuralgia (PHN) is a complication of acute herpes zoster, which is emerging as a preferred clinical trial model for chronic neuropathic pain. Although there are published meta-analyses of analgesic therapy in PHN, and neuropathic pain in general, the evidence base has been substantially enhanced by the recent publication of several major trials. Therefore, we have conducted a systematic review and meta-analysis for both efficacy and adverse events of analgesic therapy for PHN.Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
274
0
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(299 citation statements)
references
References 81 publications
(100 reference statements)
1
274
0
11
Order By: Relevance
“…93 A meta-analysis of TCAs used in the treatment of PHN (amitriptyline, nortriptyline, and desipramine) showed that significant analgesia was obtained, 79 with an earlier analysis also showing TCAs are effective in the treatment of postherpetic pain. 81 The TCAs, however, including amitriptyline (which is the most widely studied TCA for PHN therapy), have a number of adverse effects, including orthostatic hypertension, sedation, memory loss, urinary retention, constipation and cardiac conduction abnormalities.…”
Section: Antidepressantsmentioning
confidence: 98%
See 3 more Smart Citations
“…93 A meta-analysis of TCAs used in the treatment of PHN (amitriptyline, nortriptyline, and desipramine) showed that significant analgesia was obtained, 79 with an earlier analysis also showing TCAs are effective in the treatment of postherpetic pain. 81 The TCAs, however, including amitriptyline (which is the most widely studied TCA for PHN therapy), have a number of adverse effects, including orthostatic hypertension, sedation, memory loss, urinary retention, constipation and cardiac conduction abnormalities.…”
Section: Antidepressantsmentioning
confidence: 98%
“…19,89 However, antiviral therapy does not prevent pain in all patients, 79,89,90 as was also identified in an animal model. [40][41][42][43] The supplementation of antiviral therapy with corticosteroids can be beneficial.…”
Section: Clinical Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several treatments are available, PHN is very difficult to treat [44][45][46][47]. Briefly, after a baseline pain assessment has been made, the clinician should attempt to treat the patient with lidocaine patches.…”
Section: Clinical Aspects and Epidemiologymentioning
confidence: 99%